Facing the Realities of the Modern World: An Approach to Sex Education for Elementary School Children in the Digital Age - rohmah, ainur; Nanik Setyowati, Raden Roro; Jacky, M. Jacky (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2023)
In the current condition, it is important for parents to be open and ready to discuss the topic of sexuality with their children due to easy access to information through technology and to prevent sexual abuse. Parents need to be responsive in answering their children's questions about sexuality, provide accurate information that is appropriate to their children's understanding, and teach positive values related to sexuality. Comprehensive sexual education at school is also important to provide correct understanding and help children develop healthy attitudes towards sexuality. This study aims to explain how to approach sex education for elementary school children in the digital era in order to provide a comprehensive understanding of good and bad sexual knowledge and help children develop a positive attitude towards sexuality. The research method used qualitative observation and literature review techniques. The results show the need for comprehensive and responsive implementation of sexual education by parents and teachers. Parents need to be open and ready to talk about sexuality with their children. In contrast, schools need to provide sexual education that is appropriate for children's level of understanding, provide accurate information, teach positive values related to sexuality, and help children develop a healthy attitude towards sexuality.